2018
DOI: 10.1007/s00404-018-4839-9
|View full text |Cite
|
Sign up to set email alerts
|

An effect of maternal nifedipine therapy on fetoplacental blood flow: a prospective study

Abstract: Our study showed that 24 and 48 h after oral nifedipine therapy, there is a significant increase in fetal MCA and maternal uterine artery blood flow, while fetal umbilical artery and ductus venosus Doppler values do not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There are a limited number of studies that evaluate the effects of maternal nifedipine treatment on fetoplacental blood flow in maternal uterine arteries and fetal umbilical arteries. Some studies demonstrate that the maternal uterine artery and fetal umbilical artery RI values did not change significantly 48 hours after nifedipine treatment, but some studies indicate that the uterine artery RI values did change significantly 11 19 20 . Such a difference may be due to the use of different doses of nifedipine in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a limited number of studies that evaluate the effects of maternal nifedipine treatment on fetoplacental blood flow in maternal uterine arteries and fetal umbilical arteries. Some studies demonstrate that the maternal uterine artery and fetal umbilical artery RI values did not change significantly 48 hours after nifedipine treatment, but some studies indicate that the uterine artery RI values did change significantly 11 19 20 . Such a difference may be due to the use of different doses of nifedipine in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsatility index (PI) and resistance index (RI) values, which show vascular resistance parameters, were examined after nifedipine treatment, and an increase in uterine blood flow was detected [11]. Some authors, by contrast, have reported that nifedipine loading treatment does not affect fetal blood flow [12].…”
Section: Original Articlementioning
confidence: 99%
“…The studies that are available in literature to evaluate the doppler effect of Nifedipine in PE patients are scarce. However, a thorough review of databases MEDLINE/ PUBMED and Cochrane registry was done to find only three studies [11,12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differential changes in the placental and cerebral blood flow resistances may affect the cerebroplacental Doppler ratio, and the overall distribution of cardiac output. In addition, cardiac effects of nifedipine may affect the contractility and diastolic cardiac function (Namazov et al, 2018).…”
Section: Introductionmentioning
confidence: 99%